Repercussões cardiorrespiratórias agudas no uso correto de inaladores aerossóis de pó seco - Martinelli, Bruno; Pinto, Karina S.; Besse, Carolina R.; Barrile, Silvia R.; Rosa, Deborah M. C. [UNESP]; Pessoa, Bruna V. (My University, 2016)
Study model: It is a cross-over, clinical and comparative study. Objective: To evaluate the acute respiratory and cardiac respercussions in correct use of the dry powder inhalers (DPI) in patients with asthma. Methodology: Seventeen adult patients with asthma using DPI (Formoterol and Budesonide) were evaluated in two moments. The mensuared variables, before and after use of DPI, were: anthropometric, cognitive, muscle strength, vital signs, periferic oxygen saturation, respiratory pressures and peak expiratory flow. In the first moment (M1) was evaluated and monitored the usual performance before and immediately after using DPI and delivered an explicative leaflet about the correct use. In the second moment (M2), 30 days after M1, there was the same evaluation, however, with correct use of the DPI. Results: In the M2 there were increases to inspiratory pressure of 64,2±2,03 to 74,1±31,7 (cmH2O); expiratory pressure of 71,05±33,8 to 80±31,4 (cmH2O); vital capacity of 3,3±0,9 to 3,9±0,9 (l) and reductions in the pulse frequence of 80,3±10,7 to 72,2±9,4 (bm) and double product of 10001±1693 to 8846±1416 (paired t test, p<0,05). Conclusions: The correct use of the DPI promoves the positive respiratory and cardiac repercussions, improving respiratory conditions and reducing cardiac work.
Acute cardiopulmonary repercussions in the correct use of the dry-powder inhalers
Keywords: Asthma; Dry Powder Inhalers; Respiratory Therapy